Mental Health Concomitants Related to Controlling Behaviours Perpetrated by Husbands and Mothers-in-Law in Pakistan - Khan, Taalia; Österman, Karin; Björkqvist, Kaj (Technium Social Sciences Journal, 2021)
The aim of the study was to investigate mental health concomitants related to controlling behaviours perpetrated by husbands and mothers-in-law against wives in Pakistan. A questionnaire was completed by married 569 women. The mean age was 31.4 years. The women were significantly more often victimised from controlling behaviours perpetrated by the husband than by the mother-in-law. The age of the wife did not correlate with the frequency of controlling behaviours exerted by the husband but was negatively correlated with controlling behaviours perpetrated by the mother-in-law. Women who were frequently victimised by both the husband and the mother-in-law reported the significantly highest scores on anxiety, depression, obsessive compulsive symptoms, and somatisation. Those who were infrequently victimised by both the husband and the mother-in-law reported the significantly lowest scores on the same variables. Victimisation from controlling behaviours were associated with psychological concomitants. Victimisation from both the husband and the mother-in-law simultaneously shoved the highest association with psychological problems.